Psychological and Autonomic Correlates of Emotion Dysregulation among Women in Substance Use Disorder Treatment. (2nd January 2019) - Price, Cynthia J.; Crowell, Sheila E.; Pike, Kenneth C.; Cheng, Sunny Chieh; Puzia, Megan; Thompson, Elaine Adams
Abstract: Background : Emotion regulation is increasingly recognized as important for the prevention and treatment of substance use disorder (SUD). However, there is an identified lack of physiological indexes of emotion dysregulation in SUD treatment studies, critically needed to better understand the link between emotion regulation capacity (measured physiologically) and self-report health outcomes among individuals in SUD treatment. Objective : To examine the association between respiratory sinus arrhythmia (RSA) and self-report health outcomes among women in SUD treatment. Methods : This is a cross-sectional study based on baseline data from 217 women enrolled in a randomized control trial to study a mind-body intervention as an adjunct to SUD treatment. All participants were enrolled in community-based outpatient treatment. Participants were administered questionnaires to examine sample characteristics, mental health symptoms, and interoceptive awareness and mindfulness skills. RSA data was gathered as an index of emotion dysregulation. Descriptive statistics, bivariate correlations, and regression were used in the analyses. Results : Findings highlight the extensive trauma histories, low SES, and the high symptoms of distress in this sample. RSA was only significantly correlated with interoceptive awareness after controlling for age and BMI. Measures of symptomatic distress and mindfulness were not correlated with RSA. Conclusions/Importance : Results provide the first evidence of RSA as an index of interoceptive awareness in this population. The inclusion of biomarkers such as RSA in SUD clinical studies may help identify individuals that are in need of targeted treatments that include interoceptive awareness training focused on improving emotion regulation.